2016
DOI: 10.1002/hed.24362
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative goal‐directed hemodynamic management in free tissue transfer for head and neck cancer

Abstract: The goal-directed hemodynamic management algorithm decreased the ICU length of stay. Judicious use of vasoactive drugs and goal-directed fluid administration has a role in improving perioperative outcomes for patients undergoing head and neck free tissue transfer. © 2016 Wiley Periodicals, Inc. Head Neck 38: E1974-E1980, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Intraoperative and PACU fluids were administered separately by the anesthesiology and PACU staff, respectively, based on clinical judgment. 25,26 Our results suggest that these findings could be applicable to the immediate postoperative period as well. 24 Briefly, the contour of the arterial pulse wave is utilized to calculate stroke volume and vascular elastance, which in turn can provide the clinician with systemic vascular resistance.…”
Section: Limitations and Future Researchsupporting
confidence: 53%
See 2 more Smart Citations
“…Intraoperative and PACU fluids were administered separately by the anesthesiology and PACU staff, respectively, based on clinical judgment. 25,26 Our results suggest that these findings could be applicable to the immediate postoperative period as well. 24 Briefly, the contour of the arterial pulse wave is utilized to calculate stroke volume and vascular elastance, which in turn can provide the clinician with systemic vascular resistance.…”
Section: Limitations and Future Researchsupporting
confidence: 53%
“…While GDT does not necessarily result in a significant decrease in fluid administration for the treatment cohort overall, it has been argued that through its patient-specific approach, GDT reduces complications associated with excessive or restrictive fluid administration. 25 Indeed, in head and neck patient with cancer undergoing free tissue transfer, intraoperative, hemodynamic GDT has been shown to decrease ICU length of stay and increase flap survival rates. 25,26 Our results suggest that these findings could be applicable to the immediate postoperative period as well.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, both hypotension and large‐volume crystalloid administration being associated with flap failure, suggest a reevaluation of the role of vasopressors in free flap reconstruction. More rigorous fluid administration regimens targeted to noninvasive cardiac output measurement have also been trialed and failed to show an improvement in morbidity or mortality, although they have been shown to reduce length of stay for patients managed in the intensive care setting after surgery . There is a growing body of literature supporting the conclusion that vasopressors are not associated with deleterious outcomes in this type of procedure .…”
Section: Discussionmentioning
confidence: 99%
“…More rigorous fluid administration regimens targeted to noninvasive cardiac output measurement have also been trialed and failed to show an improvement in morbidity or mortality, although they have been shown to reduce length of stay for patients managed in the intensive care setting after surgery. 15,16 There is a growing body of literature supporting the conclusion that vasopressors are not associated with deleterious outcomes in this type of procedure. [17][18][19][20] Some studies of vasopressor infusions in the postoperative setting have even suggested that they may improve flap perfusion, including 1 randomized controlled trial showing no adverse effects from postoperative vasopressor administration in patients who underwent radial artery forearm flap procedures.…”
Section: Discussionmentioning
confidence: 99%